Ratings of perceived exertion at anaerobic threshold in patients with coronary artery disease - Meire Forti; Antonio Roberto Zamunér; Vandeni Clarice Kunz; Mariana Rodrigues Salviati; Tarcísio Augusto Gonçalves Nery; Ester da Silva (Universidade de São Paulo, 2014)
The study aimed to identify and compare the ratings of perceived exertion (RPE) at the ventilatory anaerobic threshold (VAT) in healthy subjects and patients with coronary artery disease (CAD). A total of 30 male subjects took part in the study and were divided into three groups: a control group (CG) composed of 10 healthy participants; a group composed of 10 participants diagnosed with CAD beta-blocker user (G-DACb); and a group composed of 10 participants with CAD non-beta-blocker user (G-DAC). The participants performed a cardiopulmonary exercise test (CPET) with continuous type ramp protocol to determine the VAT, through the visual graphical analysis (loss of parallelism between the oxygen uptake and the carbon dioxide output). During CPET, before the end of each one-minute period, the subjects were asked to rate dyspnea (RPE-D) and leg fatigue (RPE-L) on the Borg CR-10 scale. After the VAT was determined, the score that the participants gave on the Borg CR10 scale was verified. CG participants showed higher workload, oxygen uptake, carbon dioxide output, ventilation and heart rate at the VAT compared to the G-DAC and G-DACb (p<0.05). However, regarding the RPE-L and the RPE-D, no significant difference between the groups were observed (p<0.05). Values between five and six on Borg CR-10 scale matched the VAT in the subjects studied. However, other parameters must be concomitantly used for prescribing exercise intensity in physical training protocols, at levels close to the VAT for patients with CAD.